Epitaxial LaMnO3 films with remarkably fast oxygen transport properties at low temperature. Issue 21 (19th May 2021) - Rodriguez-Lamas, Raquel; Pirovano, Caroline; Stangl, Alexander; Pla, Dolors; Jónsson, Ragnar; Rapenne, Laetitia; Sarigiannidou, Eirini; Nuns, Nicolas; Roussel, Hervé; Chaix-Pluchery, Odette; Boudard, Michel; Jiménez, Carmen; et al.
Abstract : Unexpectedly high oxygen diffusion coefficients were measured for LaMnO3 at 500 °C, below its phase transition temperature, and in the range of interest for its potential use in micro Solid Oxide Fuel Cells (μ-SOFCs). Abstract : Ionic transport-related phenomena are of primary importance for the development and miniaturization of energy conversion devices such as solid oxide fuel cells and electrolysers, oxygen separation membranes and memristive devices. By using LaMnO3 (LMO) epitaxial thin films, we studied the effects of temperature, extended structural defects and strain on the oxygen mass transport properties of this parent compound perovskite by isotope exchange depth profiling. By combining the oxygen transport measurements with a detailed structural characterization using several complementary techniques, we showed that the combination of extended defects and strain relaxation accelerates the oxygen transport across the LMO film. Additionally, we demonstrated that the oxygen diffusion at 500 °C is extraordinary high due to the prevalence of the orthorhombic structure in the film, together with a high concentration of oxygen vacancies. These promising results open new perspectives for the use of LMO below its transition temperature for low temperature solid-state electrochemical applications in which oxygen diffusion is the key parameter determining the device performance.